2013
DOI: 10.1073/pnas.1222276110
|View full text |Cite
|
Sign up to set email alerts
|

Graphene microsheets enter cells through spontaneous membrane penetration at edge asperities and corner sites

Abstract: Understanding and controlling the interaction of graphene-based materials with cell membranes is key to the development of graphene-enabled biomedical technologies and to the management of graphene health and safety issues. Very little is known about the fundamental behavior of cell membranes exposed to ultrathin 2D synthetic materials. Here we investigate the interactions of graphene and few-layer graphene (FLG) microsheets with three cell types and with model lipid bilayers by combining coarse-grained molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

36
646
3
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 680 publications
(688 citation statements)
references
References 61 publications
36
646
3
3
Order By: Relevance
“…However, the underlying mechanisms of cellular internalization of GBMs remain enigmatic and several pathways have been proposed. The two main working hypotheses include phagocytosis and clathrin-mediated endocytosis 30,31 but the possibility of membrane translocation through a "piercing effect" has also been revealed from computational studies 32,33 . Remarkably, photothermal effect due to the ability of graphene to absorb NIR light was suggested to enhance the transfection efficiency thanks to induced heating which locally disrupts the organization of the lipid bilayer cell membrane, hence rendering it more permeable and facilitating endosomal escape 34 .…”
Section: What Can Gbms Offer As Gene Delivery Platforms?mentioning
confidence: 99%
“…However, the underlying mechanisms of cellular internalization of GBMs remain enigmatic and several pathways have been proposed. The two main working hypotheses include phagocytosis and clathrin-mediated endocytosis 30,31 but the possibility of membrane translocation through a "piercing effect" has also been revealed from computational studies 32,33 . Remarkably, photothermal effect due to the ability of graphene to absorb NIR light was suggested to enhance the transfection efficiency thanks to induced heating which locally disrupts the organization of the lipid bilayer cell membrane, hence rendering it more permeable and facilitating endosomal escape 34 .…”
Section: What Can Gbms Offer As Gene Delivery Platforms?mentioning
confidence: 99%
“…Recent reports on particle translocation also supported the mechanism of passive diffusion of particles into the cell membranes. 29,30 In this study, Fe 3 O 4 @C particles were observed in aggregation but not in vesicular formation; thus, they would be internalized by an energy-independent diffusion process. Further study is needed to confirm the hypothesis that the graphitic surface of the particles could cause passive diffusion of the particles into cells.…”
Section: Cytotoxicity and Cellular Uptake Of Fe 3 O 4 @Cmentioning
confidence: 56%
“…Cell lines grown in the presence of graphene show higher rate of proliferation, growth and differentiation [93] in comparison to the SiO substrate [6,94,95]. It has been reported that the use of different GO materials for cell cultures of lung epithelium have no impact on the viability and biological response of the cell [96][97][98]. NIH-3T3 fibroblasts behaviour was studied in different substrates covered with carbon nanomaterial, for example, GO, carbon nanotubes and RGO.…”
Section: Scaffolds For Mammalian Cell Culturementioning
confidence: 99%